Goodnight, seahorse - Allen-Fletcher, Carly ([Guilford, Connecticut] : Muddy Boots Press, 2018)
As a seahorse makes its way home to bed, it passes a number of other sea creatures heading off to sleep as well.
Keywords: Board books; Sea horses -- Fiction; Marine animals -- Fiction; Bedtime -- Fiction; Board books; Sea horses -- Fiction; Marine animals -- Fiction; Bedtime -- Fiction; Board books for children